Area, climate heterogeneity, and the response of climate niches to ecological opportunity in island radiations of Anolis lizards. Issue 7 (29th June 2015) - Algar, Adam C.; Mahler, D. Luke
Abstract: Aim: Rates of climate niche evolution underlie numerous fundamental ecological processes and patterns. However, while climate niche conservatism varies markedly among regions and clades, the source of this variation remains poorly understood. We tested whether ecological opportunity can stimulate radiation within climate niche space at biogeographic scales, predicting that rates of climate niche evolution will scale with geographic area and climate heterogeneity. Location: Caribbean Methods: We quantified two temperature axes (mean temperature and temperature seasonality of species' localities) of the climate niche for 130 Anolis species on Cuba, Hispaniola, Puerto Rico, Jamaica and the northern and southern Lesser Antilles. Using a species‐level phylogeny, we fitted macroevolutionary models that either constrained rates of climate niche evolution or allowed them to vary among regions. Next, we regressed region‐specific evolutionary rates against area, species richness and climate heterogeneity. We evaluated whether results were robust to uncertainty in phylogenetic and biogeographic reconstructions and the assumed mode of evolution. Results: For both niche axes, an Ornstein‐Uhlenbeck model that allowed the net rate of evolution (σ 2 ) to vary among island groups fit the data considerably better than a single‐rate Brownian motion model. Nagelkerke pseudo‐R 2 values of the fit of these OU models to mean temperature and seasonality axes were 0.43 and 0.66, respectively. Evolutionary rates for both axes were higher in larger areas, which also have more species. Only the rate of mean occupied temperature evolution was positively related to climate heterogeneity, and only after accounting for region size. Conclusions: Rates of climate niche evolution scale consistently with the area available for radiation, but responses to climate heterogeneity vary among niche axes. For the mean temperature axis, climate heterogeneity generated additional opportunities for radiation, but for seasonality it did not. Overall, the physical setting in which a clade diversifies can influence where it falls on the evolutionary continuum, from climate niche conservatism to radiation.